-
Notifications
You must be signed in to change notification settings - Fork 2
/
Copy pathNatStarProperties.agda
157 lines (136 loc) · 4.61 KB
/
NatStarProperties.agda
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
module NatStarProperties where
open import Function
open import Algebra.FunctionProperties
open import Algebra.Structures
open import Data.Empty
open import Relation.Binary.Core
open import Relation.Binary.PropositionalEquality
as PropEq
open PropEq.≡-Reasoning
open import NatStar
-- copy properties from the Agda standard library
-- Data.Nat.Properties
+-assoc : Associative _≡_ _+_
+-assoc one _ _ = refl
+-assoc (succ m) n o = begin
succ m + n + o ≡⟨ cong succ (+-assoc m n o) ⟩
succ m + (n + o)
∎
m+1+n≡1+m+n : ∀ m n → m + succ n ≡ succ (m + n)
m+1+n≡1+m+n one n = refl
m+1+n≡1+m+n (succ m) n = cong succ (m+1+n≡1+m+n m n)
+-comm : Commutative _≡_ _+_
+-comm one one = refl
+-comm one (succ n) = sym (cong succ (+-comm n one))
+-comm (succ m) n = begin
succ (m + n) ≡⟨ cong succ (+-comm m n) ⟩
succ (n + m) ≡⟨ sym (m+1+n≡1+m+n n m) ⟩
n + succ m
∎
*-distrib-right-+ : ∀ x y z → ((y + z) * x) ≡ ((y * x) + (z * x))
*-distrib-right-+ m one o = refl
*-distrib-right-+ m (succ n) o = begin
(succ n + o) * m ≡⟨ refl ⟩
m + (n + o) * m ≡⟨ cong (_+_ m) $ *-distrib-right-+ m n o ⟩
m + (n * m + o * m) ≡⟨ sym $ +-assoc m (n * m) (o * m) ⟩
m + n * m + o * m ≡⟨ refl ⟩
succ n * m + o * m
∎
*-assoc : Associative _≡_ _*_
*-assoc one n o = refl
*-assoc (succ m) n o = begin
(succ m * n) * o ≡⟨ refl ⟩
(n + m * n) * o ≡⟨ *-distrib-right-+ o n (m * n) ⟩
n * o + (m * n) * o ≡⟨ cong (λ x → n * o + x) $ *-assoc m n o ⟩
n * o + m * (n * o) ≡⟨ refl ⟩
succ m * (n * o)
∎
*-one : ∀ n -> n * one ≡ n
*-one one = refl
*-one (succ m) = cong succ (*-one m)
m*1+n≡m+mn : ∀ m n → m * succ n ≡ m + m * n
m*1+n≡m+mn one n = refl
m*1+n≡m+mn (succ m) n = begin
succ (n + m * succ n) ≡⟨ refl ⟩
succ n + m * succ n ≡⟨ cong (λ x → succ n + x) (m*1+n≡m+mn m n) ⟩
succ n + (m + m * n) ≡⟨ refl ⟩
succ (n + (m + m * n)) ≡⟨ cong succ (sym $ +-assoc n m (m * n)) ⟩
succ (n + m + m * n) ≡⟨ cong (λ x → succ (x + m * n)) (+-comm n m) ⟩
succ (m + n + m * n) ≡⟨ cong succ (+-assoc m n (m * n)) ⟩
succ (m + (n + m * n)) ≡⟨ refl ⟩
succ (m + (n + m * n))
∎
*-comm : Commutative _≡_ _*_
*-comm one n = sym (*-one n)
*-comm (succ m) n = begin
n + m * n ≡⟨ cong (λ x → n + x) (*-comm m n) ⟩
n + n * m ≡⟨ sym (m*1+n≡m+mn n m) ⟩
n * succ m
∎
*-leftIdentity : LeftIdentity _≡_ one _*_
*-leftIdentity x = refl
*-isCommutativeMonoid : IsCommutativeMonoid _≡_ _*_ one
*-isCommutativeMonoid = record
{ isSemigroup = record
{ isEquivalence = PropEq.isEquivalence
; assoc = *-assoc
; ∙-cong = cong₂ _*_
}
; identityˡ = *-leftIdentity
; comm = *-comm
}
pred : NatStar -> NatStar
pred one = one
pred (succ m) = m
≡-succ-elim : ∀ x y -> succ x ≡ succ y -> x ≡ y
≡-succ-elim x y p = cong pred p
cancel-+-left : ∀ x y z -> z + x ≡ z + y -> x ≡ y
cancel-+-left x y one p = ≡-succ-elim x y p
cancel-+-left x y (succ z) p
= cancel-+-left x y z (cong pred p)
cancel-+-right : ∀ x y z -> x + z ≡ y + z -> x ≡ y
cancel-+-right x y z p
= cancel-+-left x y z q
where q : z + x ≡ z + y
q = begin
z + x ≡⟨ +-comm z x ⟩
x + z ≡⟨ p ⟩
y + z ≡⟨ +-comm y z ⟩
z + y
∎
+-⊥-right : ∀ x y -> x ≡ x + y -> ⊥
+-⊥-right one y ()
+-⊥-right (succ x) y p
= +-⊥-right x y (≡-succ-elim x (x + y) p)
+-⊥-left : ∀ x y -> x + y ≡ x -> ⊥
+-⊥-left one y ()
+-⊥-left (succ x) y p
= +-⊥-left x y (≡-succ-elim (x + y) x p)
cancel-*-right : ∀ x y z -> x * z ≡ y * z -> x ≡ y
cancel-*-right one one z p = refl
cancel-*-right one (succ y) one p with begin
one ≡⟨ p ⟩
succ (y * one) ≡⟨ cong succ (*-comm y one) ⟩
succ (one * y) ≡⟨ cong succ refl ⟩
succ y
∎
... | ()
cancel-*-right one (succ y) (succ z) p
with +-⊥-right (succ (succ z)) (y * succ z) (cong succ p)
... | ()
cancel-*-right (succ x) one z p
with +-⊥-left (succ z) (x * z) (cong succ p)
... | ()
cancel-*-right (succ x) (succ y) z p
= cong succ (cancel-*-right x y z
(cancel-+-left (x * z) (y * z) z p))
cancel-*-left : ∀ x y z -> z * x ≡ z * y -> x ≡ y
cancel-*-left x y z p
= cancel-*-right x y z (lemma x y z p)
where lemma : ∀ x y z -> z * x ≡ z * y -> x * z ≡ y * z
lemma x y z p = begin
x * z ≡⟨ *-comm x z ⟩
z * x ≡⟨ p ⟩
z * y ≡⟨ *-comm z y ⟩
y * z
∎